Irradiated rare‐earth‐doped powellite single crystal probed by confocal Raman mapping and transmission electron microscopy. (14th April 2014) - Wang, X.; Panczer, G.; de, D.; Motto‐Ros, V.; Yu, J.; Dussossoy, J. L.; Peuget, S.; Jóźwik‐Biala, I.; Bérerd, N.; Jagielski, J.
<x xml:space="preserve">Abstract</x> The irradiation‐induced damages and structure modifications of rare earths doped powellite single crystal have been precisely studied using optical and electron microscopy techniques, including optical interferometry, confocal micro‐Raman spectroscopy and transmission electron microscopy. The surface of powellite crystal pops out anisotropically after exposing under Ar ion beam, with a saturation swelling value of 2.0% along a‐axis and 1.3% along the c‐axis of powellite at high dose. Raman mapping on focused ion‐beam sections (5 × 3 µm2) perpendicular to the irradiated surface reveals that irradiation damage induces orientation‐dependent compressive stresses in powellite. However, no significant anisotropic effect has been found on the irradiation‐induced structural disorder in powellite. At low dose (0.012 dpa), the main irradiation‐induced defects created in powellite crystal are small defect clusters. By comparison, the dominant kinds of defects in high‐dose (5.0 dpa) sample are dislocations loops and networks. Copyright © 2014 John Wiley & Sons, Ltd.